2021
DOI: 10.1029/2020ja028927
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere‐Ionosphere (A‐I) Coupling as Viewed by ICON: Day‐to‐Day Variability Due to Planetary Wave (PW)‐Tide Interactions

Abstract: It is now widely accepted that tides, planetary waves (PWs) and ultra-fast Kelvin waves (UFKW) propagating upward from the lower atmosphere play an important role in determining the longitudinal and day-to-day variability of the ionosphere. Insofar as PWs and the low-latitude ionosphere is concerned, this realization has its early roots in the work of Ito et al. (1986) and Chen et al. (1992; see also their references to the earlier Chinese literature), who first recognized the connection between quasi-2-days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…, as demonstrated through general circulation modeling by Hagan et al (2009) and Pedatella et al (2012). Forbes et al (2021) demonstrated the presence of SPW4 and SE2 in ICON/MIGHTI winds at 106 and 295 km, the potential for SE2 to propagate to F-region altitudes, and noted connections with contemporaneous topside F-region electron density variability observed by ICON. He et al (2011) emphasized the importance of SE2 trans-equatorial winds to latitudinal asymmetries of ionospheric observations.…”
Section: Se2mentioning
confidence: 82%
See 1 more Smart Citation
“…, as demonstrated through general circulation modeling by Hagan et al (2009) and Pedatella et al (2012). Forbes et al (2021) demonstrated the presence of SPW4 and SE2 in ICON/MIGHTI winds at 106 and 295 km, the potential for SE2 to propagate to F-region altitudes, and noted connections with contemporaneous topside F-region electron density variability observed by ICON. He et al (2011) emphasized the importance of SE2 trans-equatorial winds to latitudinal asymmetries of ionospheric observations.…”
Section: Se2mentioning
confidence: 82%
“…Forbes et al. (2021) demonstrated the presence of SPW4 and SE2 in ICON/MIGHTI winds at 106 and 295 km, the potential for SE2 to propagate to F‐region altitudes, and noted connections with contemporaneous topside F‐region electron density variability observed by ICON. He et al.…”
Section: Resultsmentioning
confidence: 99%
“…Forbes et al. (2021) analyzed coincident ICON measurements of neutral horizontal winds, ion drifts, and densities and demonstrated a direct link between the day‐to‐day variability of the wave‐4 structure in the E‐region and drifts and densities of ions in the F‐region ionosphere. More recently, England et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2012), and Forbes et al. (2021, 2022) demonstrate how HMEs can facilitate the interpretation of tidal winds in the 100–300 km height regime based on ICON/MIGHTI measurements.…”
Section: Introductionmentioning
confidence: 97%